2023
DOI: 10.1186/s12890-023-02347-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pulmonary hypertension in patients with hypersensitivity pneumonitis

Abstract: Background Hypersensitivity pneumonitis (HP) is an immunologically induced inflammation of the lung parenchyma that occurs in susceptible individuals in response to a variety of antigens. Repeated exposures to the causative antigens lead to chronic HP. The condition could be complicated with pulmonary hypertension (PH). Methodology 60 patients with established diagnosis of HP were included, clinical examination, high resolution computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The mechanism of PH and vasoreactivity is heterogeneous in fibrotic hypersensitivity pneumonitis. Vascular remodelling and arterial stiffening secondary to hypoxia-mediated vasoconstriction, endothelial dysfunction, and progressive fibrosis act as the main drivers of PH in fibrotic HSP 8. Elnady et al found fibrosis on CT scans to have a 49 times higher risk of developing PH than non-fibrotic HSP 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of PH and vasoreactivity is heterogeneous in fibrotic hypersensitivity pneumonitis. Vascular remodelling and arterial stiffening secondary to hypoxia-mediated vasoconstriction, endothelial dysfunction, and progressive fibrosis act as the main drivers of PH in fibrotic HSP 8. Elnady et al found fibrosis on CT scans to have a 49 times higher risk of developing PH than non-fibrotic HSP 8.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular remodelling and arterial stiffening secondary to hypoxia-mediated vasoconstriction, endothelial dysfunction, and progressive fibrosis act as the main drivers of PH in fibrotic HSP 8. Elnady et al found fibrosis on CT scans to have a 49 times higher risk of developing PH than non-fibrotic HSP 8. Vasoreactivity in non-fibrotic hypersensitivity pneumonitis has not yet been described, and the mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were demonstrated by Dybowska et al, who detected PH in 26 of 70 patients with HP (37.0%) [ 8 ]. In a recent study by Elnady et al, the frequency of PH was slightly lower (28.3%) [ 9 ]. In another study, PH was detected in 19.0% of patients with HP using sPAP 50 mm Hg as TTE diagnostic threshold [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the UIP pattern in HP patients, according to our results, was not a significant predictor of PH. In a recently published study by Elnady et al, patients with HP with and without PH also differed in the predominance of fibrosis according to HRCT [ 9 ]. Similarly, Walscher et al showed an association between the diagnosis of PH and the UIP pattern in patients with HP [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation